Characterization of leaf anatomy in species of Astrocaryum and Hexopetion (Arecaceae) - Millán, Betty (2010)
Leaf anatomy of 23 species of the genus Astrocaryum and of the two species of the genus Hexopetion is described. A total of 109 characters with at least one difference between species are reported from the lamina (83), main rib (11), petiole (9) and sheath (6). An identification key to species is given based on leaf anatomy. Distribution of the characters is discussed in order to evaluate their taxonomic relevance.